STUDY ON THE CONSUMER ACCEPTANCE TO THE REBON SHRIMP MACARONI (Acetes erythraeus) - Michael Wilson; Suparmi Suparmi; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aims to determine the formula of selected macaroni with the addition of rebon shrimp flour (Acetes erythraeus). This research consisted of 2 stages, namely making rebon shrimp flour and determining the best formulation of macaroni with the addition of rebon shrimp flour. The method used was an experiment with 4 levels of treatment with the addition of rebon shrimp flour, namely: 0 g (control), 100 g, 150 g, and 200 g with 3 replicated. Based on organoleptic test showed that rebon shrimp flour had a significant effect on the taste, aroma, texture, appearance, and color of macaroni. The addition of 100 g of rebon shrimp flour was the selected macaroni indicated by value of appearance 6.89, smell 6.93, taste 6.85, and texture 7.02. Whereas the selected macaroni contained moisture, ash, fat, and protein was 4.74%, 2.65%, 9.57% and 22.94%, respectively.Keywords: Macaroni, Addition, Rebon shrimp